ANALYSIS OF MEASUREMENT MODELS FOR THE GOVERNMENT SPENDING QUALITY AND ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Amdi Veri Darma; Pahrul Fauzi; M. Farid Alfarisy; Agus Arifin; Indrawan Firdauzi; Ajeng Faizah Nijma Ilma (Universitas Tidar, 2023)
The absence of quality spending become the main reason for government failed to provide multiplier in achieving its economic objectives. The phenomenon of budgetary slack will be likely to occur if there is no any standard to control government expenditure's success. This study aims to provide a method to identify the effectiveness of government budget by Comparing Sustainable Development Indicators as outcome and government expenditure relative to its economy as output. We also measure the rasio of government expenditure to its revenue sources as indicators of budget efficiency. Using 2021 data of SDGs indicators and government budget (both at central and regional or province government level) we found that both at the national and regional levels, the spending had been quite effective. Meanwhile for the level of budget efficiency, the central government is quite efficient, while some of regional governments were not.